Evaluation of primary hip arthroscopy complications in mid-term follow-up: a multicentric prospective study - Zeman, Petr; Rafi, Moheb; Kautzner, Jakub (International orthopaedics, 2021)
INTRODUCTION: Hip arthroscopy is a common procedure in hip preservation surgery. Its complication rate is relatively low. This prospective multicentric study evaluates complication rate in patients undergoing primary hip arthroscopy. MATERIALS AND METHODS: The study cohort consisted of 908 patients mean age of 37 years (14-67 years). Patients were prospectively included in the study in the years 2009-2017. All complications were recorded and evaluated. The minimum follow-up was 36 months. Results were statistically evaluated and risk factors for complications were identified. RESULTS: The overall complication rate was 7.3% (67/908 cases), the minor complication rate of 4.9% (45/908 cases) and the major complication rate 2.4% (22/908 cases). The most common severe complications were iatrogenic cartilage damage and instrument breakage, while the most common minor complications were perineal hypoaesthesia and heterotopic ossifications. The conversion rate to total hip replacement was 4.2% (39/908 patients). CONCLUSION: Hip arthroscopy is a safe procedure with low complication rates. Surgeon training and experience greatly influence the complication rates.
Keywords: Humans; lidé středního věku; Hip preservation; následné studie; Arthroplasty, Replacement, Hip; Aged; mladý dospělý; dospělí; Hip Joint; Arthroscopy; náhrada kyčelního kloubu; výsledek terapie; senioři; lidé; reoperace; Hip arthroscopy; Adult; Middle Aged; artroskopie; Adolescent; Treatment Outcome; Complication rate; Young Adult; Hip osteoarthritis; prospektivní studie; kyčelní kloub; Reoperation; Follow-Up Studies; mladiství; Prospective Studies